Spatial and temporal variations of childhood cancers: Literature review and contribution of the French national registry - Goujon, Stéphanie (Cancer Med, 2018)
BACKGROUND: Significant increases in childhood cancer incidence since the 1970s have been consistently reported worldwide, but the persistence of the increase on recent periods is discussed. No conclusion can be drawn concerning the spatial variations of childhood cancer, either. This study is an in‐depth investigation of the spatial and temporal variations of childhood cancer in France. An extensive review of all the studies published since 2000 on those issues is provided. METHODS: The study included 25 877 cases of childhood cancer registered nationwide over 2000‐2014. The spatial heterogeneity (overdispersion, autocorrelation, overall heterogeneity) was tested, on two geographic scales, and two spatial scan methods were used to detect clusters of cases. The annual average percent change (AAPC) in incidence rate was estimated with Poisson regression models, and joinpoint analyses were considered. RESULTS: Glioma and non‐Hodgkin lymphoma cases exhibited some spatial heterogeneity and two large clusters were detected. Overall, the incidence rate of childhood cancer was stable over 2000‐2014 (AAPC = −0.1% [−0.3%; 0.2%]). A log‐linear positive trend was significantly evidenced for gliomas other than pilocytic astrocytomas (AAPC = 1.8% [0.9%; 2.7%]), with some suggestion of a leveling‐off at the end of the period, while Burkitt lymphoma and germ cell tumor incidence rates decreased (AAPC = −2.2% [−3.8%; −0.5%] and AAPC = −1.9% [−3.4%; −0.3%], respectively). No spatial heterogeneity or significant time variation was evidenced for other cancers. CONCLUSION: Several types of childhood cancer displayed some spatial heterogeneity and two large clusters were detected, the origins of which are to be investigated and might include differences in case ascertainment. Overall, the results do not support a sustained increase in incidence rates of childhood cancer in recent years.